Haemodialysis vascular catheter‐related blood stream infection: Organism types and clinical outcomes. Issue 4 (8th February 2023) - Phillips, Jessica; Chan, Doris T.; Chakera, Aron; Swaminathan, Ramyasuda; Patankar, Khalil; Boudville, Neil; Lim, Wai H.
Abstract: Catheter‐related bloodstream infection (CRBI) is an important complication of catheter use for haemodialysis, but it remains unclear whether clinical outcomes following CRBI are influenced by organism type. This study aims to compare clinical outcomes following CRBI from Gram‐positive and non‐Gram‐positive organisms. This was a retrospective cohort study of patients with kidney failure receiving haemodialysis (HD) via vascular catheters who had a documented episode of CRBI in Western Australia between 2005 and 2018. The associations between organism type, likelihood of hospitalization, catheter removal and death from CRBI were examined using adjusted logistic regression models. There were 111 episodes of CRBI in 99 patients (6.1 episodes per 1000‐catheter‐days at risk). Of the study cohort, 53 (48%) were male and 38 (34%) identified as Aboriginal or Torres Strait Islander. Gram‐positive organisms were identified in 73 (66%) CRBI episodes, most commonly Staphylococcus aureus . Of those with non‐Gram‐positive CRBI, 9 (24%) were attributed to Pseudomonas aeruginosa . One‐hundred and two (92%) episodes of CRBI required hospitalization and 15 (13%) patients died from CRBI. Compared with non‐Gram‐positive CRBI, Gram‐positive CRBI was associated with an increased risk of hospitalization and catheter removal, with adjusted odds ratio of 9.34 (95% CI 1.28–68.03) and 3.47 (95% CI 1.25–9.67), respectively. There was no association between organism type and death from CRBI. Staphylococcus aureus remains the most common organism causing CRBI in HD patients. CRBI is associated with substantial morbidity, particularly CRBI attributed to Gram‐positive organisms. Abstract :